Sedation in Intensive Care: A review of the State-of-the-Art - S. Yu. Belyshev; A. L. Levit (Общая реаниматология, 2012)
The review deals with sedation in intensive care unit patients. It covers problems in monitoring, choice of a goal sedation level, use of a sedation pause and timely choice of medications. Key words: intensive care unit sedation, sedation scale, sedation pause, goal sedation level.